CURRENT VIEWS ON THE IMPACT OF SODIUM NITRITE AND PONCEAU 4R FOOD ADDITIVES ON THE RETINA AND THE WHOLE BODY - Synenko, V.A.; Yeroshenko, G.A.; Shevchenko, K.V.; Grygorenko, A.S.; Sokolenko, V.V.; Sharlay, N.M.; Vlasyuk, A.О. (World of Medicine and Biology, 2024)
This article examines the effects of the food additives sodium nitrite and Ponceau 4R on the retina. Both are widely used in the food industry to improve the taste, color, and shelf life of foods. However, their use has raised concerns among scientists and healthcare professionals about potential adverse health effects, particularly on the eyes. Sodium nitrite and its derivatives may cause oxidative stress and inflammation in the retina, which may lead to degenerative changes and vision loss. Although some studies suggest a neuroprotective effect of sodium nitrite, more research is needed to confirm these findings. Ponceau 4R may cause oxidative stress and inflammation in the retina, which may lead to damage to retinal pigment epithelial cells. This could potentially lead to vision loss and other eye problems.
Keywords: retina; rats; sodium nitrite; Ponceau 4R; oxidative stress